2009
DOI: 10.1017/s1368980008003418
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a redesigned iron supplementation delivery system for pregnant women in Negros Occidental, Philippines

Abstract: Objective: To determine the effectiveness of a redesigned Fe supplementation delivery system (ISDS) in improving Hb concentrations and compliance among pregnant women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 20 publications
0
18
0
3
Order By: Relevance
“…The effectiveness of any intervention which aims at improving the nutritional status of a population depends on a number of variables, including the delivery system, the recipients' compliance, as well as the characteristics of the target population [34]. Food fortification remains a promising means of addressing micronutrient deficiencies, particularly for infants and young children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effectiveness of any intervention which aims at improving the nutritional status of a population depends on a number of variables, including the delivery system, the recipients' compliance, as well as the characteristics of the target population [34]. Food fortification remains a promising means of addressing micronutrient deficiencies, particularly for infants and young children.…”
Section: Discussionmentioning
confidence: 99%
“…There are three categories of the most commonly used food vehicles employed for this purpose: staple food items (rice, oils and wheat), condiments (fish sauce, soy sauce and sugar) and processed commercial food items (infant complementary foods, dairy products and noodles) [32]. The effectiveness of any intervention that seeks to improve the nutritional status of a target population depends upon several factors, including the delivery system, the recipients' compliance and the perceived benefits [33,34]. Iron fortification of different food vehicles has been successfully used to deliver iron to large segments of the population, including flours (in Venezuela), fish sauce (in Vietnam), soy sauce (in China) and rice (in the Philippines) [31].…”
Section: Food Fortification As a Tool For Addressing Micronutrient Dementioning
confidence: 99%
“…Salah satu faktor kunci keberhasilan program IFAS di Nikaragua dan Thailand adalah tersedianya suplai tablet IFA dalam jumlah yang cukup (Sanghvi 2009). Namun, studi menunjukkan bahwa ibu hamil terkadang tidak diberikan jumlah tablet yang cukup (Risonar et al 2009;Schultink et al 1993;Titaley et al 2010). Dari studi kualitatif di Jawa Barat, ditemukan bahwa beberapa ibu memang menerima tablet IFA setiap kali melakukan ANC, namun karena jumlah yang diterima bervariasi (antara 15-30 tablet) tidak semua ibu mendapatkan total minimal 90 tablet IFA selama kehamilan (Titaley et al 2010).…”
Section: Suplai Tablet Ifaunclassified
“…Participants were controlled for strength of iron supplementation at 100 mg. 33 In a study conducted in Philippines, the percentage of women consuming iron and folic acid tablets in control group was 57.4% and in experimental group 79.2% after intervention. 21 However, the follow up of the participants was conducted for 180 days in that study, compared to 100 days in this study [considering actual follow up cases only]. The results of the study conducted in New Delhi, showed that the completion rate of participants who availed oral iron group, was 67.5% and parenteral iron group was 94.3% indicating relatively better acceptance for parenteral iron supplementation, a form of direct observance.…”
Section: Discussionmentioning
confidence: 66%
“…In this study 1180 pregnant women were given iron/folic acid tablets daily through the redesigned ISDS in the experimental areas and the existing ISDS in the control areas. 21 The impact of a weekly iron-folic acid supplement delivered with social marketing to Cambodian women in 2005, revealed that supplementation was increasingly effective among women of higher socioeconomic status (SES). Among higher SES schoolgirls, 58% took the supplements, compared with 49% for lower SES.…”
Section: Factors Contributing For Low/non-adherence To Iron Supplementsmentioning
confidence: 99%